2008
DOI: 10.1016/j.cognition.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Word order and information status in child language

Abstract: In expressing rich, multi-dimensional thought in language, speakers are influenced by a range of factors that influence the ordering of utterance constituents. A fundamental principle that guides constituent ordering in adults has to do with information status, the accessibility of referents in discourse. Typically, adults order previously mentioned referents ("old" or accessible information) first, before they introduce referents that have not yet been mentioned in the discourse ("new" or inaccessible informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 18 publications
(15 reference statements)
6
35
4
Order By: Relevance
“…Furthermore, conceptual factors like animacy and referential availability can influence the order of nouns in a conjunction when it is presented in isolation both in adults and children (Byrne & Davidson, 1985;McDonald et al, 1993;Narasimhan & Dimroth, 2008). Another challenge for the theory comes from languages that allow scrambling .…”
Section: Word Ordering Phenomena In English and Japanesementioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, conceptual factors like animacy and referential availability can influence the order of nouns in a conjunction when it is presented in isolation both in adults and children (Byrne & Davidson, 1985;McDonald et al, 1993;Narasimhan & Dimroth, 2008). Another challenge for the theory comes from languages that allow scrambling .…”
Section: Word Ordering Phenomena In English and Japanesementioning
confidence: 96%
“…This information made use of the prominence units, because the order of nouns in conjunctions have been shown to be sensitive to factors related to referential/discourse prominence (Bock & Irwin, 1980;Gleitman, January, Nappa, & Trueswell, 2007;Narasimhan & Dimroth, 2008). Just as the prominence units signaled the order of arguments in transitive and dative structures, the prominence units were also set to signal the order of nouns in conjunctions.…”
Section: Accessibility In English and Japanesementioning
confidence: 98%
“…This also points to the fact that linearization principles should not be considered independently of prosodic principles in a given language. The fact that the interaction of information status and prosodic structure may not be fully understood so far may also contribute to the heterogeneous picture that arose with respect to the impact of information structure on word order in the previous studies reported in the ‘Introduction’ (de Marneffe et al ., 2012; Hickmann et al , 1996; Narasimhan & Dimroth, 2008; Stephens, 2010). …”
Section: Experiments 2: Word Order and Definitenessmentioning
confidence: 99%
“…Narasimhan and Dimroth (2008) investigated the ordering of given and new information in three- and five-year-old German-speaking children. In their study, productions of coordinated DPs with one new and one given referent were elicited.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding word order, several studies suggest that in contrast to a cross-linguistic tendency to place given before new information in adult language, children aged three to six generally place new before given constituents, although contrasting findings have also been reported (Narasimhan and Dimroth, 2008, and references therein). In a study using the same materials and method as the present study, Sauermann et al (2011) found no general tendency for either given-before-new or new-before-given order in the productions of German 4-year-olds.…”
Section: Introductionmentioning
confidence: 99%